Placing cryptic, recently extinct, or hypothesized taxa into an ultrametric phylogeny using continuous character data: a case study with the lizard Anolis roosevelti (2015)
In recent years, enormous effort and investment has been put into assembling the tree of life: a phylogenetic history for all species on Earth. Overwhelmingly, this progress toward building an ever increasingly complete phylogeny of living things has been accomplished through sophisticated analysis of molecular data. In the modern genomic age, molecular genetic data have become very easy and inexpensive to obtain for many species. However, some lineages are poorly represented in or absent from tissue collections, or are unavailable for molecular analysis for other reasons such as restrictive biological sample export laws. Other species went extinct recently and are only available in formalin museum preparations or perhaps even as subfossils. In this brief communication we present a new method for placing cryptic, recently extinct, or hypothesized taxa into an ultrametric phylogeny of extant taxa using continuous character data. This method is based on a relatively simple modification of an established maximum likelihood (ML) method for phylogeny inference from continuous traits. We show that the method works well on simulated trees and data. We then apply it to the case of placing the Culebra Island Giant Anole (Anolis roosevelti ) into a phylogeny of Caribbean anoles. Anolis roosevelti is a “crown?giant” ecomorph anole hypothesized to have once been found throughout the Spanish, United States, and British Virgin Islands, but that has not been encountered or collected since the 1930s. Although this species is widely thought to be closely related to the Puerto Rican giant anole, A. cuvieri , our ML method actually places A. roosevelti in a different part of the tree and closely related to a clade of morphologically similar species. We are unable, however, to reject a phylogenetic position for A. roosevelti that places it as sister taxon to A. cuvieri ; although close relationship with the remainder of Puerto Rican anole species is strongly rejected by our method.